Indonesia to Target Middle East market after King Salman’ Visit - Ni Ketut Srinadi (Bali Tourism Board, 2017)
Bali is well known as the best tourist destination in the world. Beautiful sceneries along with its distinctive culture become the main attraction of foreign tourists to visit it. During this time, foreign tourists visit Bali is dominated by tourists from Australia and China. While for visitors from the Middle East countries is still relatively small. Middle Eastern tourists are well known as a potential market since they spend a lot of budget for their vacation. On March 4th to 9th 2017, Saudi Arabia’s King, King Salman Bin Abdul Aziz al Saud traveled to Indonesia with a group of 1500 people. They spend a lot of expenses while holiday in Bali in which gave a good impact on tourism industries in Bali. The King visit is expected to promote Indonesia Tourism especially Bali to his people. Providing information about a halal and friendly destination for tourists from Middle East countries is expected to attract more visitor from those countries. Since their religion is mostly Muslim. By providing detail information about halal tourism information thus it is expected the number of their visit to Indonesia, especially Bali will increase.